Making Bricks from Straw: Resources and Productivity in Health Care - Okeke, Edward N. (American Economic Review, 2026)
Why do health facilities in developing countries do so poorly? This paper examines the role of financial constraints. I describe an experiment in which we surprised health workers in randomly selected public health clinics in Nigeria with a N600,000 grant paid out in installments over one year. Its administration was left entirely to health workers. I show that the award led to large productivity gains. Using expenditure data combined with novel textual data I provide an explanation for these effects. I show that the award increased investments in physical and human capital, led to lower prices for patients and inspired health workers to do better.